Perbandingan Hasil Pengaplikasian Liquid Foundation Menggunakan Spons dan Airbrush pada Rias Wajah Pengantin Gaun Panjang - Nola Syafika Prissy; Mitra Lusiana (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Bridal makeup for long gown styles emphasized a soft and flawless look. Commonly used techniques included sponge and airbrush. The sponge absorbed more product, requiring more foundation, while the airbrush required advanced skills and specialized tools. This study aimed to compare the results of applying liquid foundation using these two techniques. A pre-experimental method with a quantitative approach was employed. The sample consisted of six individuals divided into two groups: three used the sponge technique and three used airbrush. The sampling technique was purposive sampling. Data were analyzed using normality, homogeneity, and hypothesis tests. The results show that the sponge technique yields an average smoothness of 57.1%, evenness of 61.9%, durability of 57.1%, and panelist preference of 76.1%. Meanwhile, the airbrush technique shows superior results in smoothness and evenness (76.1%), equal durability (57.1%), and panelist preference of 71.4%. Statistical analysis indicates significant differences in smoothness (p=0.001), evenness (p=0.001), and panelist preference (p=0.003), but no significant difference in durability (p=0.075).